QUALITY ASSESSMENT ON SOME SOAPS SOLD IN NIGERIA (Nigerian Journal of Technology, 2018)
Fifteen soaps were purchased from the main market in Gwagwalada Area Council of FCT, Nigeria. The soaps are Sunlight, MP3, Canoe, 4B, Glide, Lux, Joy, Imperial leather, Premier, Eva Classique, Dettol, Safeguard, Tetmosol, Septol and Premier cool. The qualities of soaps were assessed based on the following parameters; free caustic alkali, volatile matter, matter insoluble in alcohol(MIA), total fatty matter(TFM), pH, cleaning properties, washing properties and foam/lathering properties. The results obtained showed that all the soaps analyzed are good quality soaps safe for the skin. http://dx.doi.org/10.4314/njt.v37i4.37